Aufbrüche, Umbrüche, Abbrüche Wegmarken qualitativer Bildungs- und Biographieforschung - Fuchs, Thorsten; Demmer, Christine; Wiezorek, Christine (Schriftenreihe der DGfE-Kommission Qualitative Bildungs- und Biographieforschung, 2022)
The beginnings of the institutionalisation of qualitative educational and biographical research go back to 1978 and to representatives such as Dieter Baacke and Theodor Schulze, with whom qualitative research approaches found their way into educational science. Some forty years later, this volume takes a closer look at the paths of development from a theoretical and methodological perspective. What are the achievements? Which of the once formulated concerns have remained unfulfilled? What challenges, breaking points and turning points can be identified? The articles illuminate the ups, downs and upheavals of biographical pedagogy and qualitative-empirical research.